Pengaruh Varian Menu, Cita Rasa, dan Harga terhadap Keputusan Pembelian Konsumen pada Rumah Makan Cez-Ros - Rizky Ardian Saputra; Aprilia Dian Evasari; Endah Kurniawa (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to thoroughly examine the influence of menu variety, taste, and price on customers' purchasing decisions at CEZ-ROS Restaurant, located in Kediri Regency. Understanding these factors is crucial for the restaurant to enhance customer satisfaction and improve sales performance. The research employs a quantitative approach with an associative research type, designed to explore relationships between variables. The sampling technique used is accidental sampling, where respondents were selected based on convenience and their availability during the data collection period. This method allows for practical and efficient data gathering from actual restaurant customers. Data analysis involves several statistical tests to ensure accuracy and reliability. Initially, validity and reliability tests were conducted to confirm the suitability of the questionnaire. Then, multiple linear regression analysis was used to determine how menu variety, taste, and price individually and collectively influence purchasing decisions. Additionally, t-tests assessed the significance of each independent variable, while the F-test evaluated their simultaneous effect. The coefficient of determination (R²) provided insight into how much variation in purchasing decisions could be explained by these variables. The results indicate that menu variety, taste, and price significantly impact purchasing decisions both individually and together. Specifically, customers prefer restaurants offering a diverse menu, delicious food, and reasonable pricing. The F-test confirms the strong combined effect of these factors on consumer behavior. However, the coefficient of determination also suggests that while these variables are important, other external influences such as service quality, ambiance, and promotions may also affect purchasing decisions. Overall, this study highlights that CEZ-ROS Restaurant should focus on maintaining menu diversity, enhancing taste quality, and setting competitive prices to attract and retain customers effectively.